UPAYA MENINGKATKAN KETERAMPILAN KERJASAMA SISWA DENGAN MODEL PROBLEM BASED LEARNING PADA MATA PELAJARAN IPAS MATERI KEBUTUHAN MANUSIA DI KELAS IV B SDN TANAH TINGGI 09 JAKARTA PUSAT - Ayuni Kartika Putri; Julius Sagita; Indah Trismawanti (STKIP Subang, 2023)
The collaboration skills are very important skills be possessed by students. Collaboration skills are among the skills needed in the 21st century. But in reality, in the field the collaboration skills of grade IV B students of the Tanah Tinggi 09 elementary school are still lacking. So efforts are needed to improve this skill. This study aims to improve students' collaboration skills by using the Problem Based Learning (PBL) model in the social subjects of human needs material. This study uses the class action research method (PTK) which has several stages, including: observation stage, planning stage, action stage and reflection stage. The study consisted of two cycles. Each cycle amounts to two meetings. This research was conducted in grade IV of the Tanah Tinggi 09 elementary school with a total of 25 students. The data collection technique in this study was to use interviews and observations. The results showed that there was an increase in research results by 14,06%. The student completeness score in the first cycle was 73,44% and the student completeness in the second cycle increased to 87,50%. Accordingly, it can be concluded that the Problem Based Learning (PBL) model can improve students collaboration skills in social subjects material for class IV B human needs of the Tanah Tinggi 09 elementary school.